Peran Green Production dalam Pengurangan Emisi dan Optimalisasi Efisiensi Energi Industri - Ainunsari Ainunsari; Dita Rosyalita (Asian Journal of Multidisciplinary Research, 2025)
This study addresses the persistent gap in industrial sustainability whereby emission reduction efforts are often not integrated with energy efficiency optimization. The aim is to examine the role of green production in linking these two environmental outcomes within manufacturing industries. The research employs a qualitative literature-based methodology, using content analysis to synthesize findings from relevant written sources connected to green production, emission reduction, and energy efficiency optimization. The data consist of primary and secondary literature that describe key concepts, mechanisms, and reported relationships among the three focal constructs. The analysis shows that green production functions as an integrative framework through which process and operational improvements reduce energy intensity and, consequently, support emission reduction. The study concludes that effective environmental performance in manufacturing requires coherent strategies that simultaneously target energy efficiency and emissions, supported by continuous monitoring and organizational commitment.